Pengaruh Penggunaan Media Software Geogebra Terhadap Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 2 Makale - Suri Toding Lembang; Irmawaty Natsir (Musamus Journal of Mathematics Education, 2020)
This study aims to determine the effect of the use ofmedia Geogebra Software on the mathematics learning outcomes of Grade VIII students of SMP Negeri 2 Makale. Geogebra software is a dynamic program that has facilities to visualize and as a tool to construct mathematical concepts. This research is an experimental research. The population in this study were all VIII grade students of SMP Negeri 2 Makale in the 2018/2019 school year as many as 214 people. The sampling technique uses cluster random sampling with the number of samples chosen, namely 2 classes consisting of 28 students for the experimental class and 27 students for the control class. The instrument used in this study was a test of learning outcomes in the form of a description. Before and after learning both classes are given the same test. Managing research data using descriptive statistics and inferential statistics. Descriptive statistics are intended to describe student mathematics learning outcomes in the form of average scores and percentages, while inferential statistics are used to test research hypotheses. The results of the study were obtained; (1) an increase in experimental class learning outcomes with an initial average score of 18.79 increased to 73.37 with a large increase of 54.58 experienced an increase if compared to the control class with an initial average score of 15.86 increased to a large 43.31 an increase of 27.45. The increase in the average score of experimental class learning outcomes is greater than the average score of control class learning outcomes. (2) the results of thehypothesis Mann Whitney U Test show that the amymp.sig (2-tiled) value is 0,000 <0.05, then H1 is accepted. This shows that there is an influence of the use ofmedia geogebra software on mathematics learning outcomes of Grade VIII students of SMP Negeri 2 Makale.